Underreporting of influenza outbreaks in aged care facilities in South Western Sydney, Australia, 2014 - Boonwaat, Leng; Fletcher-Lartey, Stephanie; Conaty, Stephen (Western Pacific Surveillance and Response, 2016)
It is likely that delays in notification of influenza outbreaks in aged care facilities can result in increased morbidity. Timely interventions such as antiviral treatment and prophylaxis, and infection control measures are more likely to occur if Public Health Units are notified as soon as an outbreak is suspected. This brief report describes the outcome of an audit of all laboratory notified influenza cases received by the New South Wales Notifiable Conditions Information Management System (NCIMS) for cases age 65 and above originating in South Western Sydney in 2014. The audit sought to ascertain if there had been any influenza outbreaks which aged care facilities had not reported to the PHU. The report stresses the importance of having processes in place to improve early identification of influenza outbreaks in aged care facilities and to instigate outbreak control measures as soon as possible. The report also suggests that providing aged care facilities with a check list of outbreak preparedness measures that should be in place, prior to the influenza season may be a useful way of ensuring influenza outbreaks that occur in aged care facilities are notified to Public Health Units in a timely manner.